2005
DOI: 10.1002/ijc.21195
|View full text |Cite
|
Sign up to set email alerts
|

TP53 alterations and patterns of carcinogen exposure in a U.S. population‐based study of bladder cancer

Abstract: The molecular pathology of bladder cancer has been the subject of considerable interest, and current efforts are targeted toward elucidating the interrelationships between individual somatic gene loss and both etiologic and prognostic factors. Mutation of the TP53 gene has been associated with more invasive bladder cancer, and evidence suggests that TP53 mutation, independent of stage, may be predictive of outcome in this disease. However, there is no consensus in the literature that bladder carcinogen exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…There was no relationship between detection of promoter methylation and the percent of tumorous tissue in the sample (P < 0.8). This result is consistent with the previously reported finding (in the same samples) of no relationship between proportion of tumorous tissue and the measured presence of persistent TP53 protein by immunohistochemistry or TP53 mutation (16). To ensure that there was no bias in the amplification of substrate by tumor stage, we also did quantitative RT-PCR on a random subset of samples (10 invasive stage and 10 noninvasive stage) using the primers and probe for modified ACTB.…”
Section: Resultssupporting
confidence: 89%
“…There was no relationship between detection of promoter methylation and the percent of tumorous tissue in the sample (P < 0.8). This result is consistent with the previously reported finding (in the same samples) of no relationship between proportion of tumorous tissue and the measured presence of persistent TP53 protein by immunohistochemistry or TP53 mutation (16). To ensure that there was no bias in the amplification of substrate by tumor stage, we also did quantitative RT-PCR on a random subset of samples (10 invasive stage and 10 noninvasive stage) using the primers and probe for modified ACTB.…”
Section: Resultssupporting
confidence: 89%
“…Several carcinogens, for ex- ample ultraviolet light, aflatoxin B 1 and cigarette smoke, have been found to cause mutations in the TP53 gene in some types of cancer, including bladder cancer [12][13][14] . Feasibly, some of the DNA damage related to such environmental agents is repaired by DNA repair enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…These relatively common SNPs are thought to contribute to variations in DNA repair capacity [6][7][8][9] . The enzymes coded by these genes are considered to repair DNA damaged by some carcinogens causing mutations in the TP53 gene [12][13][14] . Thus, we selected these DNA repair genes as the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this experiment, the bladder cancer tissues in rat models treated with nicotine at different concentrations were detected for the expression of mt-p53 and the results showed that mt-p53 was positively expressed in the bladder cancer tissues and the expression was enhanced with the concentration of nicotine increasing. In the clinical studies related to p53 and bladder cancer, some scholars [11][12][13][14][15] confirmed that p53 gene mutations are closely related to the grade and stage of bladder cancer. If the tumor has p53 gene alteration, poor prognosis, shorter survival time and a higher mortality rate are usually shown.…”
Section: Discussionmentioning
confidence: 82%